Financial technology and bank risk-taking behavior: a case of selected South African banks - Magula, Zizipho (Rhodes University, Faculty of Commerce, Department of Economics)
In this study, our analysis contributes to the emerging literature investigating if the introduction of FinTech enhances or diminishes the effect of the bank risk determinants in the South African banking sector and establish if FinTech can be a channel that affects bank risk-taking behaviour in South Africa. Using data collected from Thomson Reuters and the South African Reserve Bank covering the top ten South African banks based on the availability of data on all variables, we provide detailed evidence on the effects of FinTech on risk-taking behaviour of banks and the effects of FinTech on bank determinants such as Non-performing loans (NPL). Still, scant empirical research has investigated whether FinTech start-ups cause banks to increase their risk- taking behaviour to remain relevant, competitive and maintain their market share. From an economic perspective, it is crucial to close the research gap to understand better how FinTechs reshape the banking sector, the financial sector, and the economy by analyzing the effects of FinTech on bank characteristics. The study shows that banks' risk-taking behaviour is increased when the FinTech financial planning platform is introduced in the selected banks. Secondly, the effects of NPLs are enhanced through the following, which in turn affects the bank risk: 1. Credit dummy variable when the money market dummy variable is introduced in banks. 2. The interaction of NPL and the transfer dummy variable when the FinTech credit segment is introduced in banks. 3. Money market dummy variable and NPL interaction when the credit and transfer segment is introduced in banks. The findings of this study add to the advancement of bank and FinTech literature and provide new opportunities for future research, particularly in the South African context. Finance specialists may be interested in the changes that FinTechs make in the financial sector, while economists may investigate the implications for the overall economy or required policy reforms.
Keywords: Development finance; Fintech; Banks and banking -- South Africa; Non-performing loan; Risk-taking behaviour